Feasibility study of O-X coupling for overdense plasma heating through O-X-B mode conversion in FTU - Bin, W.; Bruschi, A.; D'Arcangelo, O.; Galperti, C.; Granucci, G.; Moro, A.; Nowak, S.; Pucella, G. (Nuclear fusion, 2013)
The subject of this paper is the feasibility study of electron Bernstein wave heating (EBWH) at 140 GHz through the O-X-B double mode conversion in a plasma of the Frascati Tokamak Upgrade (FTU) device. The high-density profiles of the FTU plasma are shown and the results of the simulations of O-X coupling carried out with a dedicated ray-tracing code are presented. The simulations are aimed at finding the optimal launching conditions and to calculating the maximum coupling efficiency achievable with the FTU parameters. Also the effects predicted by a recent theoretical model available in the literature, which accounts for a description of the inhomogeneities of the toroidal plasma more realistically than a slab model, are evaluated. The parameters of the launched beam considered in the paper are those permitted with the new electron cyclotron resonance heating front steering launcher of FTU.